O direito penal e o princípio da proibição de proteção deficiente: a face oculta da proteção dos direitos fundamentais - Streck, Maria Luíza Schafer (Universidade do Vale do Rio do Sinos, 2008)
Several changes have occurred in the legally protected interest field, based on the assumption that the progress of Criminal Law cannot be seen separately from the trajectory of Modern State and, as a result, constitutionalism. State, originally absolutist, overcomes its deficits whereas develops the protection of rights, passing from "enemy" to "friend" of fundamental rights. In fact, the absenteeism of Liberal State led to state interventionism, typical of Welfare State. Although it has been an advance for the rights, its conception still neglected the democracy and fundamental rights which originated the Democratic State of Law, whose paradigm is a huge advance in the State and Law models. From this idea, this work intends to develop the comprehension about Untermassverbot to recover the ignored side of proportionality and fundamental rights. For this reason, its applicabilities are presented in the Criminal Law field, altering from jurisdictional analyze to legislative perspective of unconstitutionalities
Keywords: direitos fundamentais; estado democrático de direito; princípio da proibição de proteção deficiente; direito penal; democratic state of law; fundamental rights; untermassverbot; criminal law; Ciências Sociais Aplicadas